2011
DOI: 10.1080/09540121.2010.498859
|View full text |Cite
|
Sign up to set email alerts
|

The roles of labor migrants' wives in HIV/AIDS risk and prevention in Tajikistan

Abstract: This study aimed to build formative knowledge regarding labor migrants' wives' knowledge, attitudes, and behaviors regarding HIV/AIDS risk and protection that would inform developing innovative HIV prevention strategies. This was a collaborative ethnography in Tajikistan that included minimally structured interviews and focused field observations with 30 Tajik wives in Dushanbe married to Tajik male migrant workers currently working in Moscow. The results documented the wives' concerns over their husbands’ saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 16 publications
1
25
0
2
Order By: Relevance
“…Second, the study findings provide evidence that challenges some important commonly held beliefs about preventing HIV among migrants’ wives in Tajikistan (33). Previous research found that wives frequently believe that: 1) their husbands are not visiting sex workers in Russia; 2) if their husbands have a regular partner in Moscow, then they will not visit sex workers, and: 3) their migrant husbands can be trusted to protect them from HIV/AIDS.…”
Section: Discussionmentioning
confidence: 68%
“…Second, the study findings provide evidence that challenges some important commonly held beliefs about preventing HIV among migrants’ wives in Tajikistan (33). Previous research found that wives frequently believe that: 1) their husbands are not visiting sex workers in Russia; 2) if their husbands have a regular partner in Moscow, then they will not visit sex workers, and: 3) their migrant husbands can be trusted to protect them from HIV/AIDS.…”
Section: Discussionmentioning
confidence: 68%
“…Studies show that labour migrants to Russia may be at risk for HIV infection due to their risky sexual behaviour including unprotected sex with sex workers (Amirkhanian et al 2011; Weine, Bahromov, and Mirzoev 2008). Tajik migrants who become infected in Russia may act as a bridge for HIV transmission between Russia and Tajikistan, infecting their wives when they return home (Golobof et al 2011; Kramer et al 2008; WHO 2008). The multi-level HIV risks associated with migration have been established in prior research, and include prolonged and frequent separation from their wives, difficult living and working conditions, peer expectations for sexual partnering, limited social control in migrant communities, reliance on sex workers, low levels of HIV-related knowledge, low perceived HIV risk, and limited condom use (Brockerhoff and Biddlecom 1999; Côté et al 2004; Magis-Rodriguez et al 2009; Puri and Cleland 2006; Shaw et al 2013; Wolffers et al 2002; Xu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This clearly pointing to a gap between 'knowing and acting' a phenomenon also noted among wives of Tajik migrants. 24 and wives of male Mexican migrants to the United States of America. 25 The main reason which inhibits migrants' wives of Nepal from negotiating on safer sex is historically and culturally entrenched gender-based discrimination in every domain of life.…”
mentioning
confidence: 99%